Capital Structure and Financial Performance of Malaysian Construction Firms - Mohammad, Hapsah S; Bujang, Imbarine; Hakim, Taufik Abd (Asian Economic and Financial Review, 2019)
This study investigated the impact of capital structure on financial performance of Malaysian construction firms. The empirical data was taken from 41 construction firms listedon the main board of Bursa Malaysia and observed from 2011 to 2015. Capital structure is the financing decision on the proportion between debt and equity. The right proportion leads to optimal capital structure. This study adopts two theories namely trade-off theory and pecking order theory, to explain the concept of optimal capital structure. Capital structure is the independent variable and is measured by short-term debt (STD), long-term debt (LTD), total debt (TD), meanwhile the dependent variable, financial performance, is proxy by return on asset (ROA) and return on equity (ROE). The results indicated positive and significant association between LTD and ROE. However, STD was significant but negatively correlated with ROE. Meanwhile, TD was positive but insignificantly associated with ROE. Nevertheless, STD, LTD and TD were negatively and insignificantly associated with ROA. The findings suggested that financing decisions are influenced by the objective of the firms. If the goal of the firms was to maximize return on asset, the pecking order theory was employed, however if the firms’ objective was to maximize return on equity then the trade-off theory was appropriate to explain the concept of optimal capital structure. The concentration on one industry and the relatively narrow five-year period for data collection were the main limitations of this study. The findings of the research will contribute towards capital structure literature.